The Role of Human Resource Management in Enhancing Employee Engagement at PT Nestlé Indonesia - Rismanto Caesar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to analyze the role of human resource management (HRM) in enhancing employee engagement at PT Nestlé Indonesia. Employee engagement is considered a key factor influencing employee performance, productivity, and loyalty toward the organization. This research employs a descriptive–qualitative approach by examining HRM practices, including recruitment, training and development, compensation systems, and performance management. The findings indicate that the implementation of integrated HRM strategies fosters a conducive work environment, boosts employee motivation, and strengthens a sense of belonging to the organization. Furthermore, career development support and effective communication between management and employees play an essential role in building work engagement. Thus, HRM at PT Nestlé Indonesia contributes significantly to creating sustainable employee engagement, which ultimately has a positive impact on the achievement of the company’s goals.